1992
DOI: 10.1207/s15327752jpa5801_3
|View full text |Cite
|
Sign up to set email alerts
|

The Factor Structure and Criterion Validity of the Short Form of the Eating Attitudes Test

Abstract: One of the more frequently used measures of eating disorders is the 40-item Eating Attitudes Test (EAT) developed by Garner and Garfinkel (1979). Although originally designed to diagnose anorexia nervosa, the test has recently been applied to nonclinical populations also. In this study, we examined psychometric and validity data for a short version of the scale, the EAT-26. Using a sample of 809 female soldiers in their late teens, results showed that the EAT-26 is reliable, the factor structure is different f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
115
0
3

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(133 citation statements)
references
References 0 publications
12
115
0
3
Order By: Relevance
“…Therefore, different versions of the EAT exist in the literature: comprising three factors [6][7][8], four factors [9][10][11], five factors [12,13] or seven factors [14]. Second, researchers often encounter items that do not load on any factor [7,8], items that cross-load on other scales [13], or items that weave between scales [10].…”
Section: Eat-26 Structure/eat-26 Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, different versions of the EAT exist in the literature: comprising three factors [6][7][8], four factors [9][10][11], five factors [12,13] or seven factors [14]. Second, researchers often encounter items that do not load on any factor [7,8], items that cross-load on other scales [13], or items that weave between scales [10].…”
Section: Eat-26 Structure/eat-26 Assessmentmentioning
confidence: 99%
“…Despite the fact that researchers using both exploratory [10,14] and confirmatory [8,11] factor analyses have reported different factorial structures of the EAT-26, several repeating patterns have been observed. First, the same three items ('Feel that others would prefer if I ate more', 'Other people think that I am too thin', and 'Feel that others pressure me to eat') are commonly grouped into factors labeled 'Perceived social pressure to eat' [12,14], 'Others' perceptions' [13], 'Important others' [7], or simply 'Social pressure' [6,9].…”
mentioning
confidence: 98%
“…26,27 This study used the shorter version (26 items), which has a 6-point item scale that was found to be highly correlated (r ¼ .98) with the original version. 27 EAT-26 was validated in Hebrew by Koslowsky et al, 28 with good reliability (a ¼ 0.79). For the present study, the EAT-26 was translated into Russian by a professional translator and back-translated by another native Russian speaker to check for accuracy.…”
Section: Samplesmentioning
confidence: 99%
“…Although the original EAT-40 was designed to measure symptoms specifically of AN, it is now considered a validated measure of undifferentiated DSM-IV ED (Mintz & O'Halloran, 2000). The EAT has also been regarded as one of the most widely used self-report measures of ED (Koslowsky et al, 1992;Patton & King, 1991). The EAT-26/40 has been used in a variety of clinical and research settings including North American and European samples, multiple age brackets and across genders (Garner et al, 1982;King, 1989;King, 1991;Dalle, Grave, De Luca, & Oliosi, 1997;Dotti & Lazzari, 1998).…”
Section: Eating Attitudes Test (Eat) the Eat-26 Is An Abbreviated Vementioning
confidence: 99%
“…The EAT-26 does not contain any items that explicitly do not reflect DSM-5 criteria. Koslowsky et al (1992) examined the psychometric properties and validity data for the EAT-26 and found reliable results. Cronbach's coefficient alpha was found to be .83 for the EAT-26.…”
Section: Eating Attitudes Test (Eat) the Eat-26 Is An Abbreviated Vementioning
confidence: 99%